Propagation and in vitro tuberization of two varieties of potato (2018)
This study was conducted in the Laboratorio de Cultivo de Tejidos Vegetales of the Universidad Pedagógica y Tecnológica de Colombia with the purpose of acquiring knowledge on the behavior under in vitro conditions as to evaluate a methodology for the micropropagation of plantlets and the production of microtubers from two varieties of potato ( Solanum tuberosum L. ssp andigena) Diacol Capiro and Parda Pastusa. The nodal segments provided by the ICA were disinfected with 10 % NaOCl, Then cultured for multiplication in MS medium and MS+NAA (0.02 mg/L). For the rooting process, NAA or IBA was added into the culture medium or applied in 30 seconds pulses. Subsequently, micropropagated uninodal segments were cultured in tuberization medium, showing an increase in production when supplemented with BA (2.5 mg/L) and with 8 % saccharose in the two varieties. The protocols developed in this study allow a large number of micropropagated plantlets and production of microtubers of Diacol Capiro and Parda Pastusa; the plantlets and microtubers developed can be cultured under controlled conditions for the production of pre-basic seeds.